Antithrombotic materials
By using a (meth)acrylate copolymer composed of alkyl (meth)acrylates, metoxypolymerene glycol (meth)acrylates and silicane (meth)acrylates, the problem of degradation of anti-hemocoagulation performance during long-term contact with blood is solved, and the effect of high biocompatibility and durability is achieved.
Patent Information
- Application Number
- JP2023511408
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-31
- Filing Date
- 2022-03-29
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-03-29
AI Technical Summary
Existing medical devices have difficulty maintaining the durability and hemocompatibility of anti-hemoglobin materials when exposed to blood for a long time.
A (meth)acrylate copolymer consisting of alkyl (meth)acrylates, metoxypolymerene glycol (meth)acrylates and silicane (meth)acrylates is used to improve its anti-hemoglobin performance on medical devices by adjusting the residual monomer and degradation viscosity in the copolymer.
The material exhibits high biocompatibility and durability when contacting the blood, which can effectively inhibit platelet aggregation and complement system activation, and extend the anti-hemoglobin effect.
Smart Images

Figure 0007647876000001 
Figure 0007647876000002 
Figure 0007647876000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an antithrombotic material that imparts blood compatibility to medical devices. More specifically, the present invention relates to a (meth)acrylate copolymer containing a hydrophobic (meth)acrylate and a hydrophilic (meth)acrylate, the (meth)acrylate copolymer containing at least a silicone (meth)acrylate as the hydrophobic (meth)acrylate, being water-insoluble and in a viscous liquid state at room temperature. Contains (meth)acrylate copolymers This invention relates to antithrombotic materials. [Background technology]
[0002] In recent years, medical devices using various polymeric materials have been under study, and they are expected to be used in blood filters, artificial kidneys, plasma separation, catheters, artificial lungs, artificial blood vessels, adhesion prevention membranes, artificial skin, etc. In these cases, synthetic materials, which are foreign to the living body, will be used in contact with tissues and blood in the living body, so the medical devices must be biocompatible.
[0003] When medical devices are used as materials that come into contact with blood, the following three factors are important for biocompatibility: (a) inhibition of the blood coagulation system, (b) inhibition of platelet adhesion and activation, and (c) inhibition of activation of the complement system. Among these, when used as materials that come into contact with blood for a relatively short time, such as medical devices for extracorporeal circulation (e.g., artificial kidneys and plasma separation membranes), anticoagulants such as heparin and sodium citrate are generally used simultaneously, so the inhibition of activation of platelets and the complement system (b) and (c) above is particularly important.
[0004] The applicant has investigated materials suitable for the above-mentioned use, and has filed an application for an antithrombotic material comprising a (meth)acrylate copolymer consisting of an alkyl (meth)acrylate, a silicone (meth)acrylate, and a methoxypolyethylene glycol (meth)acrylate, which has a number average molecular weight of 2,000 to 200,000, is water-insoluble, is a viscous liquid at room temperature, is soluble in any alcohol having 1 to 6 carbon atoms, and has a viscosity of 0.5 to 10,000 Pa s at 37°C (Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 4793700 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide an antithrombotic material which can be used as a material that is in contact with blood for a relatively long period of time compared to conventional medical materials and has improved durability against contact with blood. [Means for solving the problem]
[0007] The present inventors have found that a copolymer obtained by copolymerizing an alkyl (meth)acrylate, a methoxypolyethylene glycol (meth)acrylate, and a silicone (meth)acrylate, in which the residual monomer amount and reduced viscosity are adjusted to specific ranges, can be applied to a medical device to impart antithrombogenicity for a longer period than in the past, and have completed the present invention. That is, the present invention has the following configuration.
[0008] (1) A (meth)acrylate copolymer having a weight average molecular weight of 50,000 or more and 1,500,000 or less, which is obtained by copolymerizing an alkyl (meth)acrylate unit represented by the following general formula 1, a silicone (meth)acrylate unit represented by the following general formula 2, and a methoxypolyethylene glycol (meth)acrylate unit represented by the following general formula 3 in a molar ratio of 80 to 20 / 10 to 0.01 / 10 to 79.99, and which is water-insoluble (here, being water-insoluble means that An antithrombotic material comprising a (meth)acrylate copolymer which is a viscous liquid at room temperature, soluble in any one of alcohols having 1 to 6 carbon atoms, has a residual monomer amount of 4,000 ppm or less, and has a reduced viscosity (ηsp / c) of 0.18 dl / g or more and 3.00 dl / g or less (when 1 mass % of the (meth)acrylate copolymer is allowed to stand in 99 mass % physiological saline at 37°C for 30 days), and is a viscous liquid at room temperature, soluble in any one of alcohols having 1 to 6 carbon atoms, has a residual monomer amount of 4,000 ppm or less, and has a reduced viscosity (ηsp / c) of 0.18 dl / g or more and 3.00 dl / g or less. [ka] (In the formula, R 1 is an alkyl group having 8 to 12 carbon atoms, R 2 represents a hydrogen atom or a methyl group) [ka] (In the formula, R 3 is a hydrogen atom or a methyl group, R 4 is an alkylene group having 1 to 6 carbon atoms, R 5 represents an alkyl group having 1 to 6 carbon atoms, and n represents an integer of 1 to 30. [ka] (In the formula, R 6 represents a hydrogen atom or a methyl group, and n represents an integer of 2 to 4. (2) A medical device containing the antithrombotic material described in (1). Effect of the Invention
[0009] The antithrombotic material of the present invention is a material that is excellent in biocompatibility and has high durability against contact with blood. In addition, since the physical properties of the material are a water-insoluble viscous substance, even if the antithrombotic material supported on a medical device comes into contact with blood, it does not easily dissolve into the blood, and the medical device can maintain its antithrombotic properties for a long period of time. Furthermore, since the material contains silicone (meth)acrylate as a hydrophobic (meth)acrylate, its water-repellent effect is expected to suppress hydrolysis of the (meth)acrylate copolymer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In the present invention, the (meth)acrylate copolymer containing a hydrophobic (meth)acrylate and a hydrophilic (meth)acrylate is preferably a liquid having durability against blood contact and viscosity at room temperature. Here, durability against blood contact means that when the (meth)acrylate copolymer is immersed in an alcohol immersion treatment solution at room temperature for 16 hours, a certain amount of the (meth)acrylate copolymer remains and exhibits antithrombotic properties. If a certain amount of the (meth)acrylate copolymer remains after immersion in an alcohol immersion treatment solution at room temperature for 16 hours, it can be determined that the copolymer has (maintains) sufficient antithrombotic properties even when contacted with blood at 37°C for 30 days. In addition, since the copolymer is liquid at room temperature but viscous, it has the advantage of being able to suppress elution into blood when used as a coating on medical devices, etc.
[0011] In the present invention, the hydrophilic (meth)acrylate preferably contains a methoxypolyethylene glycol (meth)acrylate represented by the following general formula 3. In the following general formula 3, it is preferable to use one having 2 to 10 ethylene oxide units, more preferably 2 to 5. Specific examples include methoxydiethylene glycol (meth)acrylate, methoxytriethylene glycol (meth)acrylate, methoxytetraethylene glycol (meth)acrylate, methoxypentaethylene glycol (meth)acrylate, methoxyhexaethylene glycol (meth)acrylate, methoxyheptaethylene glycol (meth)acrylate, methoxyoctaethylene glycol (meth)acrylate, methoxynonaethylene glycol (meth)acrylate, and methoxydecaethylene glycol (meth)acrylate. If the repeating unit becomes too large and hydrophilicity increases too much, copolymerization may occur. If Since it dissolves more into the blood of the body, it may easily be detached from the medical material. Therefore, methoxytetraethylene glycol (meth)acrylate with 4 repeating ethylene oxide units and methoxytriethylene glycol (meth)acrylate with 3 repeating ethylene oxide units are more preferable. Methoxytriethylene glycol (meth)acrylate with 3 repeating ethylene oxide units is particularly preferable.
[0012] In the present invention, the hydrophobic (meth)acrylate preferably contains a silicone (meth)acrylate represented by the following general formula 2. The silicone (meth)acrylate to be used is preferably a silicone (meth)acrylate having 1 to 50 dimethylsiloxane repeating units. If the repeating units are too large, the viscosity of the resulting copolymer may become too high, making it difficult to handle. If the repeating units are too small, the viscosity may become too low, and the copolymer may easily disappear from the coating surface of a medical device or the like. Therefore, the number of dimethylsiloxane repeating units is more preferably 1 to 20. [ka] (In the formula, R 3 is a hydrogen atom or a methyl group, R 4is an alkylene group having 1 to 6 carbon atoms, R 5 represents an alkyl group having 1 to 6 carbon atoms, and n represents an integer of 1 to 30.
[0013] In the present invention, the hydrophobic (meth)acrylate may contain other hydrophobic (meth)acrylates in addition to the silicone (meth)acrylate. The other hydrophobic (meth)acrylates are not particularly limited, but it is preferable to add, as an example, a hydrophobic (meth)acrylate represented by the following general formula 1. In the following general formula 1, R 1 The number of carbon atoms used is preferably 8 to 20, and more preferably 8 to 12. Specific examples of such hydrophobic (meth)acrylates include normal hexyl (meth)acrylate, cyclohexyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, and stearyl (meth)acrylate, with 2-ethylhexyl (meth)acrylate and lauryl (meth)acrylate being particularly preferred from the viewpoints of cost and performance. [ka] (In the formula, R 1 is an alkyl group having 8 to 12 carbon atoms, R 2 represents a hydrogen atom or a methyl group.)
[0014] Representative examples of the water-insoluble (meth)acrylate copolymer of the present invention include silicone (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-normal hexyl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-normal hexyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-normal hexyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-normal hexyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-cyclohexyl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-cyclohexyl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, acrylate-methoxytriethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-cyclohexyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-phenyl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-phenyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-phenyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-n-octyl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-n-octyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-n-octyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-n-octyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer,Silicone (meth)acrylate-2-ethylhexyl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-2-ethylhexyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-2-ethylhexyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-lauryl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer acrylate copolymer, silicone (meth)acrylate-lauryl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-lauryl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-n-nonyl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-n-nonyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate Copolymer, silicone (meth)acrylate-n-nonyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-n-decyl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-n-decyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-n-decyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer Polymers, silicone (meth)acrylate-stearyl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymers, silicone (meth)acrylate-stearyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymers, silicone (meth)acrylate-stearyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymers, silicone (meth)acrylate-lauryl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymers,Examples of the (meth)acrylate copolymer include, but are not limited to, silicone (meth)acrylate-lauryl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-lauryl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-myristyl (meth)acrylate-methoxydiethylene glycol (meth)acrylate copolymer, silicone (meth)acrylate-myristyl (meth)acrylate-methoxytriethylene glycol (meth)acrylate copolymer, and silicone (meth)acrylate-myristyl (meth)acrylate-methoxytetraethylene glycol (meth)acrylate copolymer, which are alkyl (meth)acrylate units represented by the following formula 1, silicone (meth)acrylate units represented by the following formula 2, and methoxypolyethylene glycol (meth)acrylate units represented by the following formula 3 in a molar ratio of 80-20 / 10-0.01 / 10-79.99. If the amount of hydrophobic (meth)acrylate is too small, the copolymer will be easily dissolved in blood, etc., and if the amount is too large, the blood compatibility of the hydrophilic (meth)acrylate may not be fully exhibited. Therefore, the molar ratio is more preferably 80 to 50 / 5 to 0.01 / 15 to 49.99, more preferably 77 to 55 / 5 to 0.01 / 18 to 44.99, and even more preferably 73 to 57 / 5 to 0.01 / 22 to 42.99.
[0015] There are number average molecular weight and weight average molecular weight as indicators of the molecular weight of a copolymer, but since weight average molecular weight has a greater effect on stability and adhesion, weight average molecular weight was selected as the indicator in the present invention. If the weight average molecular weight is too small, not only is there a risk of easy elution in blood, but also the strength and stability of the coating film may be lost. In addition, the larger the weight average molecular weight, the higher the viscosity when preparing a coating solution, which has the secondary effect of improving adhesion to the coating substrate. Therefore, the weight average molecular weight of the (meth)acrylate copolymer is more preferably 60,000 or more. In addition, it is preferable that the weight average molecular weight of the (meth)acrylate copolymer is 1,500,000 or less, because the workability when coating the (meth)acrylate copolymer on a medical device or the like is improved. More preferably, it is 1,000,000 or less, and even more preferably 500,000 or less. Here, the weight average molecular weight is the sum of the molecular weights of all molecules divided by the sum of the molecular weights, and is one of the indicators of polymer properties. Setting the weight average molecular weight of this (meth)acrylate copolymer to be 50,000 or more and 1,500,000 or less is also a very important technical requirement for achieving specific technical objectives regarding purification of the copolymer, handling of the treatment liquid, suitability for medical devices, stability of the coating film, etc. Methods for measuring the weight-average molecular weight include end group quantitative analysis, osmometry, vapor pressure osmometry, vapor pressure depression method, freezing point depression method, boiling point elevation method, gel permeation chromatography (GPC) method, etc., but in the present invention, the commonly used method of gel permeation chromatography (GPC) method is adopted from the viewpoint of ease of operation.
[0016] In the present invention, the reduced viscosity (ηsp / c) of the (meth)acrylate copolymer is preferably 0.18 dl / g or more and 3.00 dl / g or less. By using a copolymer (antithrombotic material) having such a viscosity range, when it is coated on a medical device such as an artificial heart-lung circuit or a catheter, the adhesion between the copolymer and the medical device is excellent, and antithrombotic properties can be maintained even during long-term use. A more preferable reduced viscosity range is 0.18 dl / g or more and 1.50 dl / g or less, and even more preferably 0.18 dl / g or more and 0.50 dl / g or less.
[0017] In addition, in the present invention, the hydrophobic (meth)acrylate does not necessarily include silicone (meth)acrylate. However, as can be seen from its basic structure, silicone has excellent heat resistance and cold resistance, and has a low glass transition temperature (Tg), so it has the advantage of being able to exhibit stable characteristics over a variety of temperature ranges. In addition, it has the advantage of being resistant to acids and alkalis and being highly chemically stable because of its large bond energy. Furthermore, it has excellent copolymerizability with (meth)acrylate monomers, and can be preferably used as a raw material for the (meth)acrylate copolymer of the present invention. Silicone (meth)acrylate has been recognized as a material that is highly safe for living organisms, and has been adopted as a material for contact lenses in recent years. Therefore, it is believed that the content of silicone (meth)acrylate in the antithrombotic material is not too high to cause a problem, and a silicone (meth)acrylate-methoxypolyethylene glycol (meth)acrylate copolymer may also be used. However, currently, the raw material price of silicone (meth)acrylate is relatively high, and using silicone (meth)acrylate alone as the hydrophobic (meth)acrylate may be disadvantageous in terms of cost-effectiveness. Considering the performance, quality, cost, etc. comprehensively, it is sufficient that the upper limit of the amount of silicone (meth)acrylate added is 50% by mass or less. More preferably, it is 40% by mass or less, and even more preferably, it is 35% by mass or less. In addition, silicone (meth)acrylate may be mixed with other alkyl (meth)acrylates as described above. On the other hand, if the content of silicone (meth)acrylate is too small, hydrolysis may progress during storage, and the long-term stability as an antithrombotic material may decrease, so the content of silicone (meth)acrylate in the hydrophobic (meth)acrylate is more preferably 0.1% by mass or more, even more preferably 0.5% by mass or more, and even more preferably 1.0% by mass or more.
[0018] This (meth)acrylate copolymer may be a copolymer in which the monomer of the above general formula 2 and the monomer of the general formula 3 are arranged alternately, but when analyzed from the total amount, it may also be a copolymer consisting of a segment or block consisting of a hydrophobic monomer and a segment or block consisting of a hydrophilic monomer. It can be assumed that the segment or block consisting of a hydrophobic monomer may have a complex structure such as a so-called microphase separation structure or a mosaic pattern structure, in which the segment or block consisting of a hydrophilic monomer functions to fix the segment or block consisting of a hydrophilic monomer. In any case, although the molecular weight of the copolymer and the type and characteristics of the hydrophilic monomer may have some influence, if the amount of the hydrophobic monomer is slightly increased, the elution of the segment or block consisting of the hydrophilic monomer of the copolymer can be suppressed. In addition, increasing the amount of the hydrophobic segment slightly is thought to also function to increase the affinity with hydrophobic medical devices, and it can be assumed that it plays an advantageous role in adhering to the medical device as a coating. Although the behavior regarding the presence or absence of segments and the state of their affinity cannot be accurately verified based on technical grounds at present, the copolymer is a polymer material with a friendly affinity to living organisms.
[0019] Methoxypolyethyleneglycol (meth)acrylate homopolymers are highly hydrophilic and therefore have excellent blood compatibility, but because they are water-soluble, there is a problem that they gradually dissolve when in contact with blood, etc. for a long period of time. The present inventors have conducted extensive research into materials that are not only highly blood compatible but also durable for long-term use, and have found that a copolymer obtained by imparting appropriate hydrophobicity to prevent dissolution into blood, etc., and flexibility to prevent physical peeling of the coating film can solve the problem. Thus, the copolymer contained in the treatment liquid is substantially composed of two kinds of monomer components that fulfill two different interfacial functions, that is, a hydrophilic monomer, segment, or block having functions such as antithrombogenicity and anti-elution properties for blood, and a hydrophobic monomer, segment, or block having functions such as affinity and adhesion properties for medical devices. On the other hand, the monomers, segments, or blocks that constitute the copolymer complement each other in the molecular structure, and the copolymer is stable against elution, dispersion, etc. of It also appears to form bonds or structures.
[0020] In the present invention, the (meth)acrylate copolymer is preferably soluble in any of alcohols having 1 to 6 carbon atoms. It is more preferable that the (meth)acrylate copolymer is soluble in alcohols having 1 to 3 carbon atoms, since this facilitates drying after coating. Here, soluble means that when 1 g of the (meth)acrylate copolymer is immersed in 10 ml of the alcohol at 25° C., at least 90 mass % of the (meth)acrylate copolymer dissolves within 16 hours at room temperature.
[0021] In the present invention, the antithrombotic material made of a (meth)acrylate copolymer may contain an antibacterial substance, etc. The antibacterial substance is not particularly limited, and examples thereof include ampicillin, nafcillin, amoxicillin, oxacillin, azlocillin, penicillin G, carbenicillin, penicillin V, dicloxacillin, pheneticillin, floxacillin, piperacillin, mecillin, sulbenicillin, methicillin, ticarcillin, mezlocillin, cefaclor, cephalothin, cefadroxil, cephapirin, cefamandole, cephradine, cefatrizine, cefsulodin, and cefazolin. , ceftazidime, ceforanide, ceftriaxone, cefoxitin, cefuroxime, cephacetrile, latamoxef, cephalexin, amikacin, neomycin, dibekacin, kanamycin, gentamicin, netilmicin, kanamycin, tobramycin, amphotericin B, novobiocin, bacitracin, nystatin, clindamycin, polymyxin, colistin, rovamycin, erythromycin, streptomycin, spectinomycin, lincomycin, bacitra ... Antibiotics such as cyclosporine, chlortetracycline, oxytetracycline, demeclocycline, rolitetracycline, doxycycline, tetracycline, and minocycline; antifungal agents such as amphotericin B, ketoconazole, clotrimazole, miconazole, econazole, natamycin, flucytosine, nystatin, and griseofulvin; isobutyl parahydroxybenzoate, isopropyl parahydroxybenzoate, ethyl parahydroxybenzoate, and butyl parahydroxybenzoate. , paraoxybenzoic acid esters such as propyl paraoxybenzoate, biguanide compounds such as chlorhexidine, surface active compounds such as benzethonium, benzalkonium, lauryl sulfate, alkyl polyaminoethyl glycine, fatty acids, domiphen bromide, phenol derivatives such as thymol, phenol, hexachlorophene, resorcinol, boric acid compounds such as boric acid and borax, iodine compounds such as iodine, iodoform, povidone iodine, metals such as gold, silver, copper, mercury, thimerosal, vinegar Metal compounds such as silver sulfadiazine, acrinol, methyl rosa NiliExamples of the antibacterial substance include antibacterial pigment compounds such as benzoquinone, and sulfa drugs such as mafenide acetate, sulfadiazine, sulfisomidine, and sulfamethoxazole. These antibacterial substances may be salt compounds such as sodium salts, potassium salts, magnesium salts, calcium salts, hydrochlorides, sulfates, and gluconates, and two or more kinds of antibacterial substances may be used in combination.
[0022] The above antibacterial substances can be broadly classified into water-soluble and water-insoluble ones, and representative examples of water-soluble antibacterial substances include benzalkonium chloride, povidone-iodine, penicillin G potassium, streptomycin sulfate, etc. Representative examples of water-insoluble antibacterial substances include silver sulfadiazine, chlorhexidine, etc.
[0023] In the present invention, when a medical device or the like is coated with an antithrombotic substance (copolymer) and a poorly water-soluble antibacterial substance, the elution of the antibacterial substance becomes extremely small and continuous, and long-term antibacterial properties can be maintained, although it is unclear whether this is because the copolymer is water-insoluble or because the water-insolubility of the copolymer and the poor water-solubility of the antibacterial substance function complementarily. On the other hand, when a copolymer and a water-soluble antibacterial substance are coated, the copolymer is water-insoluble, but the antibacterial substance is water-soluble, so the elution amount is greater than that when a poorly water-soluble antibacterial substance is used, and although instantaneous strong antibacterial properties can be expressed, long-term antibacterial properties cannot be maintained. For example, intravascular catheters, infusion tubes, artificial lungs, etc. are medical devices that are used continuously for one to several days, and long-term antibacterial properties are required for such applications. In addition, by combining a water-soluble antibacterial substance with a poorly water-soluble antibacterial substance, it is also possible to impart multi-stage antibacterial properties, such as initially exerting strong bactericidal power by the water-soluble antibacterial substance and then exerting long-term antibacterial properties by the poorly water-soluble antibacterial substance. If this multi-stage antibacterial property is applied to an intravascular catheter, the water-soluble antibacterial substance will be eluted early and will exhibit strong antibacterial properties, thereby sterilizing the normal skin bacteria that may be brought into the blood vessel when the catheter is inserted, reducing the risk of infection during insertion. Furthermore, while the catheter is indwelling, the long-term antibacterial properties of the poorly water-soluble antibacterial substance will be able to prevent bacteria from settling on the catheter and the proliferation of bacteria that have invaded from the insertion site, reducing the risk of infection during placement.
[0024] In the present invention, the antibacterial substance is preferably 0.01% by mass or more and 70% by mass or less, more preferably 0.05% by mass or more and 50% by mass or less, even more preferably 0.1% by mass or more and 30% by mass or less, and even more preferably 0.1% by mass or more and 10% by mass or less, based on the mass of the antithrombotic composition. If the content of the antibacterial substance is too low, the antibacterial properties of the antibacterial substance may not be fully exhibited. If the content of the antibacterial substance is too high, the medical device may have a poor appearance after surface treatment such as coating, or the elution of the antibacterial substance into the body may increase, causing local inflammation due to the eluted antibacterial substance. Therefore, the antibacterial substance may be present on the entire surface of the medical device, but it is preferable to have it present only in the vicinity of the insertion part that penetrates the skin in order to suppress local inflammation.
[0025] The antithrombotic material of the present invention may be any of a random copolymer, a block copolymer, and a graft copolymer. The copolymerization reaction for producing the antithrombotic material of the present invention is not particularly limited, and known methods such as radical polymerization, ionic polymerization, photopolymerization, and polymerization using a macromer can be used.
[0026] As an example of the method for producing the (meth)acrylate copolymer of the present invention, a production method by radical polymerization will be described below. For example, a monomer, a polymerization solvent, and an initiator are added to a stirrable reaction apparatus equipped with a reflux tower, and the polymerization is initiated by heating after nitrogen replacement, and the polymerization is allowed to proceed by maintaining that temperature for a certain period of time. A chain transfer agent can also be used during this polymerization to control the molecular weight. The solvent is removed from the solution after the polymerization is completed to obtain a crude (meth)acrylate copolymer. The crude (meth)acrylate copolymer obtained is then stirred in a poor solvent for purification. The purification process is repeated once or several times to increase the purity of the (meth)acrylate copolymer. The copolymer obtained in this manner is then dried.
[0027] As the polymerization solvent used in the copolymerization, alcohols such as methanol, ethanol, isopropyl alcohol, organic solvents such as ethyl acetate, toluene, benzene, methyl ethyl ketone, or water can be used, but in the present invention, ethyl acetate, methanol, ethanol, etc. are preferably used in terms of the solubility of the monomer and the resulting copolymer and ease of availability. In addition, a mixture of a plurality of the above solvents can be used. The mass ratio of these polymerization solvents to the monomer is preferably 20 to 90 / 60 to 10, more preferably 30 to 90 / 70 to 10, and even more preferably 35 to 85 / 65 to 15. If the charge ratio is within the above range, the polymerization reaction rate can be maximized.
[0028] As the polymerization initiator, peroxide-based and azo-based radical initiators generally used in radical polymerization are used. Examples of peroxide-based radical initiators include inorganic peroxides such as potassium persulfate, ammonium persulfate, and hydrogen peroxide, and organic peroxides such as benzoyl peroxide, t-butyl hydroperoxide, and cumene peroxide. Examples of azo-based radical initiators include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-aminodipropane) dihydrochloride, dimethyl 2,2'-azobisbutyrate, and dimethyl 2,2'-azobis(2-methylpropionate). Redox initiators in which a peroxide-based initiator is combined with a reducing agent can also be used. These polymerization initiators are preferably added in an amount of 0.01% by mass or more and 1% by mass or less to the monomer in the polymerization solution. More preferably, the amount added is 0.05% by mass or more and 0.5% by mass or less, and even more preferably 0.05% by mass or more and 0.3% by mass or less. By setting the amount of the polymerization initiator and the like to be added within the above range, a copolymer having an appropriate weight average molecular weight can be obtained with a good monomer reaction rate.
[0029] The temperature during polymerization varies depending on the type of solvent and the type of initiator, but it is preferable to use a temperature close to the 10-hour half-life temperature of the initiator. Specifically, when the initiator is used, the temperature is preferably 20°C or higher and 90°C or lower. More preferably, the temperature is 30°C or higher and 90°C or lower, and even more preferably, the temperature is 40°C or higher and 90°C or lower. As a chain transfer agent used to control the molecular weight during polymerization, high-boiling thiol compounds such as dodecyl mercaptan, thiomalic acid, and thioglycolic acid, isopropyl alcohol, phosphorous acid, hypophosphorous acid, etc. can be used.
[0030] In the present invention, the (meth)acrylate copolymer is produced by copolymerizing hydrophilic and hydrophobic monomers, and therefore has both hydrophilic and hydrophobic properties. Therefore, in the solution after copolymerization, components consisting of the hydrophilic monomer (methoxypolyethylene glycol (meth)acrylate) and the hydrophobic monomer (silicone (meth)acrylate, and sometimes alkyl (meth)acrylate), which are unreacted monomers, and the (meth)acrylate copolymer are mixed. In order to isolate the water-insoluble (meth)acrylate copolymer from this mixture, for example, the copolymer solution can be purified by dropping it into a solvent that dissolves the hydrophilic monomer, and then the copolymer can be purified using a solvent that dissolves the hydrophobic monomer. In addition, the (meth)acrylate copolymer can be efficiently recovered by using a reprecipitation poor solvent in which alcohol and water are mixed in a specific ratio. Furthermore, in the solution in which the polymerization reaction is completed, a mixture of alcohol and water in a specific ratio is added to the solution, and the (meth)acrylate copolymer is separated from the solution. A poor solvent is converted into a water-insoluble (meth)acrylate copolymer. It is also possible to employ a purification method in which the (meth)acrylate copolymer is separated by adding the washing solution and stirring at a constant temperature, and then the precipitate is recovered by decantation, and the same method is repeated by adding a washing solution.
[0031] In the present invention, the poor solvent used for purifying the copolymer is preferably a poor solvent that does not dissolve the copolymer but dissolves both the hydrophilic and hydrophobic monomers.
[0032] In the present invention, the alcohol used in the reprecipitation treatment is preferably an alcohol having 1 to 10 carbon atoms, more preferably an alcohol having 1 to 7 carbon atoms, and even more preferably an alcohol having 1 to 4 carbon atoms. Specific examples of such alcohols include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, 2-methoxy-1-propanol, and tertiary butanol, with methanol, ethanol, 1-propanol, and 2-propanol being more preferred because they can be dried at low temperature and in a short time.
[0033] In the present invention, the amount of residual monomer (amount of monomer unreacted in polymerization) is important because it is related to safety. Naturally, by reducing the amount of residual monomer in the antithrombotic material, the standard set forth in the guidelines regarding elution from medical devices can be cleared, but an unexpected effect was that by reducing the amount of residual monomer to a very low level of 4,000 ppm or less, it was possible to increase the adhesion and retention of the antithrombotic material on the surface of the medical device. In addition, the ratio of the amount of polymer obtained to the amount of monomer input is expressed as the recovery rate. By carrying out the above-mentioned purification treatment once, or 2 to 8 times as necessary, it is possible to recover a water-insoluble (meth)acrylate copolymer with an unreacted monomer content of 4,000 ppm or less at a high recovery rate of 30 mass% or more. If the content of unreacted monomers, oligomers, and polymerization residues contained in the copolymer is high, they may dissolve into the blood and become causative substances for shock symptoms of patients. Most of these causative substances can be removed by purification treatment, but considering the safety of patients, it is more preferable to make the content 3,000 ppm or less, even more preferably 2,000 ppm or less, and particularly preferably 1,000 ppm or less.
[0034] The volume ratio of the crude (meth)acrylate copolymer of the present invention to the poor solvent is preferably 1:1 to 1:20, more preferably 1:3 to 1:10. When the volume ratio is within the above range, the purification efficiency and the recovery rate can be maximized.
[0035] The temperature during purification of the crude (meth)acrylate copolymer of the present invention is preferably 30 to 60° C., more preferably 40 to 60° C. When the temperature during purification is within the above range, the viscosity of the crude (meth)acrylate copolymer is reduced by heating, making it easier to separate it from the poor solvent, and the recovery rate of the (meth)acrylate copolymer can be maximized.
[0036] In the present invention, if the recovery rate of the (meth)acrylate copolymer after purification exceeds 90% by mass, there is a risk of unreacted monomers being contained in the recovered material, and if it is below 20% by mass, the production efficiency decreases, so the recovery rate is preferably 20-90% by mass. Although keeping the recovery rate at 20-90% by mass means losing or discarding some of the copolymer, this is unavoidable in terms of preventing the inclusion of unreacted monomers as much as possible. This is because, given the unique circumstances of the copolymer having both hydrophilic and hydrophobic properties to be applied to medical devices, such consideration must naturally be taken.
[0037] In order to use the purified copolymer to impart antithrombotic properties to medical devices, it is necessary to remove the solvent by drying. For example, drying can be performed at 60°C under reduced pressure of 1 Torr or less. If sufficient drying is not achieved, drying under reduced pressure can be continued.
[0038] The antithrombotic material of the present invention described above is water-insoluble and can be preferably used as a surface treatment agent for medical devices and the like. As a specific embodiment, the antithrombotic material can be obtained by dissolving the obtained antithrombotic material in an organic solvent, applying the solution obtained to the surface of a substrate of a medical device or the like, and then removing the solvent. Methods for supporting the antithrombotic material of the present invention on the surface of a substrate include known methods such as a coating method, a method using graft polymerization by radiation, electron beams, or ultraviolet rays, and a method using a chemical reaction with a functional group of the substrate. Among them, the coating method is practically preferable because the manufacturing process is easy. The coating method is not particularly limited, and a coating method, a spray method, a dip method, and the like can be used. For example, the coating method using the coating method can be performed by a simple operation such as immersing a substrate in a coating liquid in which the antithrombotic material of the present invention is dissolved in a suitable organic solvent such as alcohol, chloroform, acetone, tetrahydrofuran, or dimethylformamide, removing excess solution, and then air-drying. It is also preferable to apply heat to the substrate after coating to dry it. This can further increase the adhesion between the substrate and the antithrombotic material of the present invention and fix them more firmly.
[0039] The organic solvent to be used is one that will cause as little damage as possible to the medical device substrate. Specifically, methanol, ethanol, isopropyl alcohol, normal propyl alcohol, acetone, normal hexane, cyclohexane, tetrahydrofuran, 1,4-dioxane, cyclohexanone, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, etc. are used. Among these, methanol, ethanol, and isopropyl alcohol are more preferred because they have low boiling points and are easy to dry after coating.
[0040] The (meth)acrylate copolymer obtained by copolymerizing the alkyl (meth)acrylate and / or silicone (meth)acrylate of the present invention with methoxypolyethylene glycol (meth)acrylate has an appropriate balance between hydrophilicity and hydrophobicity, and can therefore be suitably used as a blood-compatible material. In particular, a (meth)acrylate copolymer containing a specific range of silicone (meth)acrylate can suppress the adsorption and adhesion of blood proteins, etc., and can therefore be suitably used as a treatment material for medical devices and artificial organs. In addition, the (meth)acrylate copolymer of the present invention can be used alone or in a mixture of two or more kinds.
[0041] When a medical device treated with this antithrombotic material comes into contact with blood, the highly hydrophilic methoxypolyethylene glycol (meth)acrylate protrudes from the surface and exerts its antithrombotic properties, while the hydrophobic (meth)acrylate remains near the base material, preventing direct contact between the blood and the medical device.
[0042] As a method for confirming the durability of the present antithrombotic material against dissolution in blood, there is a method of immersing the material in alcohol at room temperature. It is preferable to use a mixed solvent of methanol and ethanol. Since a solvent in which methanol and ethanol are mixed at a mass ratio of 80 / 20 has a slightly stronger dissolution power than blood, the durability of the antithrombotic property can be evaluated by immersing the antithrombotic material in the mixed solvent for 16 hours.
[0043] In the present invention, the (meth)acrylate copolymer has the property of being insoluble in methanol but soluble in ethanol. When methanol and ethanol are mixed in a predetermined ratio as an alcohol immersion treatment solution for confirming durability after 30 days of blood contact at 37°C (sustained antithrombogenicity), durability after 30 days of blood contact at 37°C can be confirmed even in as short a time as 16 hours. The mass ratio of methanol to ethanol in the alcohol immersion treatment solution is preferably 90-60:10-40, more preferably 90-70:10-30. In addition, in a test using an evaluation sheet described later, adhesion of blood clots is low, that is, the number of evaluation sheets on which adhesion of blood clots was confirmed after immersion in a solvent is 1 or less out of 10 evaluation sheets, and the (meth)acrylate copolymer is 0.1 μg / cm 2 If this level remains, it can be determined that the material has sufficient durability.
[0044] In the present invention, a blood coagulation test can be mentioned as one of the methods for evaluating the blood compatibility of (meth)acrylates. Specifically, this utilizes a reaction in which fibrin in plasma gels with calcium ions to form a fibrin gel. The blood compatibility of a polymer can be confirmed by checking the presence or absence of blood clots after immersion in water in calcium ion-added plasma that has come into contact with a sample. The less blood clots that adhere, the higher the blood compatibility. In the evaluation using evaluation sheets described below, if blood clots are confirmed to adhere to 4 or less sheets out of 10 evaluation sheets, the blood compatibility can be determined to be good.
[0045] In the present invention, a method for calculating the coating amount of a sample includes quantification by NMR. Specifically, the substrate coated with the sample is extracted with ethanol, the extract is dried, and then NMR measurement is performed to calculate the coating amount from the area of the corresponding peak. Durability can be evaluated by comparing the coating amount before and after alcohol immersion treatment. After immersing an evaluation sheet in 99.5 mass % ethanol, the remaining amount of the (meth)acrylate copolymer was 3.0 μg / cm 2 If the above value is met, it can be determined that the antithrombotic effect can be sufficiently exhibited at the initial stage of blood contact.
[0046] A medical device at least partially coated on the surface with the antithrombotic material of the present invention can exhibit excellent antithrombotic properties. Examples of such medical devices include blood filters, blood storage containers, blood circuits, indwelling needles, catheters, guide wires, stents, artificial lung devices, dialysis devices, adhesion inhibitors, wound dressings, adhesives for biological tissues, and repair materials for regenerating biological tissues. In particular, a medical device having an extracorporeal circulation circuit and a blood contact portion therein is a preferred embodiment.
[0047] Here, the base material for medical devices includes all materials that are commonly used. That is, polyvinyl chloride, polycarbonate, polyethylene terephthalate, polyethylene, polypropylene, poly-4-methylpentene-1, thermoplastic polyether polyurethane, thermosetting polyurethane, silicone rubber such as polydimethylsiloxane having a crosslinking portion, polymethyl methacrylate, polyvinylidene fluoride, polytetrafluoroethylene, polysulfone, polyethersulfone, polyacetal, polystyrene, ABS resin and mixtures of these resins, metals such as stainless steel, titanium, and aluminum, etc. The antithrombotic material of the present invention has a balanced material composition, molecular weight, viscosity, etc., and also has optimized coating conditions, so that it is possible to coat uniformly and firmly regardless of the material, shape, surface properties, etc. to be coated.
[0048] In the present invention, the method for supporting the antithrombotic material on the medical device is not particularly limited, but for example, the medical device may be immersed in a treatment liquid in which the antithrombotic material is dissolved or dispersed in an organic solvent or the like, and then the solvent may be removed by heating or the like. The concentration of the (meth)acrylate copolymer in the treatment liquid is preferably 0.001% by mass or more and 10% by mass or less. If the concentration of the (meth)acrylate copolymer is too low, for example, when applied to a medical device, there is a possibility that the performance will not be fully expressed, so it is more preferable that the concentration is 0.01% by mass or more. In addition, if the concentration is too high, there is a risk that the solution viscosity will increase too much and the workability will decrease, so it is preferably 5% by mass or less. EXAMPLES
[0049] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.
[0050] (Evaluation of alcohol solubility) After adding 1 g of sample to a 50 mL vial, 99 g of ethanol was added and thoroughly mixed. After 30 minutes, dissolution was confirmed by visual inspection. When no ethanol-insoluble matter was visible, it was judged as ○ (good), and when ethanol-insoluble matter was visible, it was judged as × (bad).
[0051] (Evaluation of Water Insolubility) To the solution judged to have alcohol solubility of ○ (good), 100 g of water was added and mixed. If the cloudiness did not disappear even after 30 minutes of continued mixing, it was judged to be ○ (good), and if the cloudiness disappeared after 30 minutes of continued mixing, it was judged to be × (bad).
[0052] (Measurement of weight average molecular weight) 15 mg of sample was weighed into a vial, 3.0 mL of mobile phase for GPC measurement was added, and the mixture was left to stand overnight. The solution was filtered through a 0.45 μm hydrophilic PTFE membrane filter cartridge (Millex-LH, Nihon Millipore). For GPC measurement, a 515 HPLC pump and a 717plus automatic injection device (Nihon Waters) were used, and a 2×PLgel 5μMIXED-D, 7.5×300 mm column (Agilent Technologies) was used. The column temperature was 40°C, and the mobile phase was tetrahydrofuran for liquid chromatography containing dibutylhydroxytoluene as a stabilizer (Fujifilm Wako Pure Chemicals). Detection was performed with RI, and 20 μL was injected. Molecular weight calibration was performed with monodisperse polystyrene (Easi Cal PS-1, Agilent Technologies).
[0053] (Measurement of reduced viscosity) 1 g of sample was weighed out into a glass bottle, and 15 mL of acetone (Fujifilm Wako Pure Chemical) was added. The sample was mixed by shaking by hand once every 20 minutes. After 1 to 2 hours, it was confirmed by visual inspection that the sample had dissolved, and the sample was transferred to a 25 mL measuring flask. After washing, acetone was added to make 25 mL. The solution was then filtered through a 5 μm filter (Merck) to obtain the test solution. Using an Ubbelohde viscometer with a viscometer constant C = 0.003426 (cSt / s), the drop times of the sample solution and acetone at 30°C were measured, and the reduced viscosity was calculated using the following formula 1. (A / B-1) / C=(A / B-1) / (S / 25×100)=(A / B-1) / (S×4) A: Time it takes for the sample solution to fall (seconds) B: Time it takes for acetone to fall (seconds) S: Sample weight (g) C: Sample solution concentration (g / dL)
[0054] (Measurement of mass loss) The weighing bottle was placed in an electric furnace set at 105°C and dried for 30 minutes. It was then allowed to cool in a desiccator for 20 minutes, and the mass of the weighing bottle was measured. 0.5 g of sample was weighed into the weighing bottle. Similarly, the weighing bottle was placed in an electric furnace set at 105°C and dried for 2 hours. It was then allowed to cool in a desiccator for 20 minutes, and the mass of the weighing bottle was measured. The mass loss (%) was calculated from the obtained mass of each weighing bottle. If the mass loss (%) was 5% or less, it was determined that the sample was sufficiently dried.
[0055] (Measurement of Residual Monomer Amount) 0.2 g of sample was dissolved in 2 mL of acetone (Fujifilm Wako Pure Chemicals), diluted appropriately, and the residual monomer was quantified by GC measurement. The measurement device used was a GC-2010Plus (Shimadzu), and the column was an Rtx-5 (GL Sciences). The inlet temperature was set at 150°C, the detector temperature at 280°C, and the oven temperature at 40°C. It was determined that the purification was sufficient if the residual monomer was 4,000 ppm or less.
[0056] (Measurement of copolymer composition ratio) 20 mg of the sample was dissolved in 1 mL of deuterated chloroform and analyzed by a 400 MHz superconducting Fourier transform nuclear magnetic resonance spectrometer (400-MR, Agilent). 1 H-NMR measurements were performed.
[0057] (Preparation of evaluation sheet) Ethanol was added to the sample to make a total of 100 g, and ethanol solutions of various concentrations were prepared to obtain treatment liquids. The concentrations of the samples prepared are shown in Table 2. After immersing half (2 cm x 2 cm x 0.1 cm) of a polycarbonate sheet (4 cm x 2 cm x 0.1 cm) in the treatment liquid for 10 seconds, the polycarbonate sheet was removed and dried on both sides for 30 seconds each with air at a flow rate of 10 mL / min. The sheet was then dried at room temperature for 16 hours to obtain an evaluation sheet.
[0058] (Blood coagulation test) 800μL of preserved rabbit blood (model number: 003-00053-01, Japan Bio-Cellulum Co., Ltd.) was added to a 15mL centrifuge tube. 66.6μL of 80mM calcium chloride solution was added and thoroughly stirred to prepare the test blood solution. The evaluation sheet was placed on a plastic petri dish. The plastic petri dish was placed on a water bath set at 37℃. 200μL of the test blood solution was added to the untreated and treated parts of the evaluation sheet. It was then incubated at 37℃ for 25 minutes. After incubation, the evaluation sheet was submerged in 100mL of physiological saline (Otsuka Pharmaceutical Co., Ltd.) and gently shaken. The number of blood clots attached to the surface of the evaluation sheet that was pulled out of the physiological saline was confirmed. If blood clots were confirmed to be attached to 4 or less of the 10 evaluation sheets, the blood compatibility was judged to be good.
[0059] (Coat Quantitative Test) The evaluation sheet was immersed in 5 mL of ethanol (99.5% by mass) for 30 minutes to obtain an extract. Nitrogen gas was sprayed onto the obtained extract at 40°C, and the extract was dried to a solid state until the odor of ethanol disappeared. This operation was repeated three times. 0.13 mg of dimethyl isophthalate was added to the entire amount of the obtained dried product, which was then dissolved in 0.6 mL of deuterated chloroform and stirred at 30°C. 1H-NMR measurement was carried out. The coating amount was calculated from the obtained peak area. The coating amount was calculated using the following formula. Coating amount = C x 218.023 x B x 1000000 ÷ 19400 ÷ A A: Sample weight B: Weight of dimethyl isophthalate C: The integral value of the peak derived from methoxytriethylene glycol acrylate when the integral value of the peak derived from 1,3-dimethyl-2-imidazolidinone is set to 100.
[0060] (Alcohol immersion treatment test) The evaluation sheet was immersed in 150 mL of an alcohol immersion treatment solution (methanol:ethanol = 80% by mass: 20% by mass) for 16 hours. After immersion, the evaluation sheet was sufficiently dried and the above-mentioned blood coagulation test and coating quantification were performed in the same manner.
[0061] Example 1 471.8 g of methoxytriethylene glycol acrylate (MTEGA) (Shin-Nakamura Chemical Co., Ltd.), 78.0 g of silicone methacrylate (PDMSMA) (Gelest, product name: MCR-M11), and 694.5 g of 2-ethylhexyl acrylate (EHA) (Toa Gosei Co., Ltd.) were added with 1.2325 g of azobisisobutyronitrile (AIBN) (Fujifilm Wako Pure Chemical Co., Ltd.), and polymerization reaction was carried out at 85 ° C for 3 hours in 1628.3 g of ethanol (Kishida Chemical Co., Ltd.). After the polymerization reaction was completed, the mixture was dried at normal pressure at 85 ° C for 2 hours. Then, the mixture was dried under reduced pressure at 60 ° C for 1 hour to obtain a concentrate. The concentrate was divided into two equal parts, concentrate A and concentrate B. Next, 3162.7 g of methanol (Kishida Chemical Co., Ltd.) and 305.3 g of water were added to 612.1 g of concentrate A, and the mixture was stirred for 30 minutes. After the stirring, the mixture was left to stand for 1.5 hours, and the supernatant was removed by decantation. Methanol was added to this precipitate, and the mixture was stirred for 30 minutes. After the mixture was left to stand for 1.5 hours, the supernatant was removed by decantation. This operation was repeated three times to obtain precipitate A. The amount of methanol used was 3161.7g, 3161.4g, and 3163.9g, respectively. Similarly, 3162.3g of methanol and 303.1g of water were added to 614.4g of concentrate B, and the mixture was stirred for 30 minutes. After the stirring, the mixture was left to stand for 1.5 hours, and the supernatant was removed by decantation. Methanol was added to this precipitate, and the mixture was stirred for 30 minutes. After the mixture was left to stand for 1.5 hours, the supernatant was removed by decantation. This operation was repeated three times to obtain precipitate B. The amount of methanol used was 3165.5g, 3167.5g, and 3165.4g, respectively. The obtained precipitate A and precipitate B were combined and dried under reduced pressure at 40°C for 1.5 hours to obtain copolymer 1.
[0062] Example 2 94.25g of methoxytriethylene glycol acrylate (MTEGA) (Shin-Nakamura Chemical Co., Ltd.), 15.59g of silicone methacrylate (PDMSMA) (Gelest, product name: MCR-M11) and 138.68g of 2-ethylhexyl acrylate (EHA) (Toa Gosei Co., Ltd.) were added with 0.2469g of azobisisobutyronitrile (AIBN) (Fujifilm Wako Pure Chemical Co., Ltd.), and polymerization reaction was carried out at 85°C and 3 hours in 165.18g of ethanol (Kishida Chemical Co., Ltd.). After the polymerization reaction was completed, the mixture was dried at normal pressure at 85°C for 1 hour. Then, the mixture was dried under reduced pressure at 60°C for 1.5 hours to obtain a concentrate. The concentrate was divided into two equal parts, concentrate A and concentrate B. Next, 631.97g of methanol (Kishida Chemical Co., Ltd.) was added to 122.51g of concentrate A, and the mixture was stirred at 60°C for 30 minutes. After the stirring, the mixture was left to stand for 1.5 hours, and the supernatant was removed by decantation. Methanol was added to this precipitate, and the mixture was stirred at 60°C for 30 minutes. After the mixture was left to stand for 1.5 hours, the supernatant was removed by decantation. This operation was repeated three times to obtain precipitate A. The amounts of methanol used were 631.98g, 632.03g, and 632.05g, respectively. Similarly, 631.99g of methanol was added to 122.50g of concentrate B, and the mixture was stirred at 60°C for 30 minutes. After the stirring, the mixture was left to stand for 1.5 hours, and the supernatant was removed by decantation. Methanol was added to this precipitate, and the mixture was stirred at 60°C for 30 minutes. After the mixture was left to stand for 1.5 hours, the supernatant was removed by decantation. This operation was repeated three times to obtain precipitate B. The amounts of methanol used were 631.98g, 632.00g, and 632.01g, respectively. The obtained precipitates A and B were combined and dried at normal pressure at 85° C. for 30 minutes, and then dried under reduced pressure at 40° C. for 1 hour to obtain copolymer 2.
[0063] Comparative Example 1 94.25g of methoxytriethylene glycol acrylate (MTEGA) (Shin-Nakamura Chemical Co., Ltd.), 15.59g of silicone methacrylate (Gelest, product name: MCR-M11), and 138.68g of 2-ethylhexyl acrylate (EHA) (Toa Gosei Co., Ltd.) were added with 0.247g of azobisisobutyronitrile (AIBN) (Fujifilm Wako Pure Chemical Co., Ltd.), and polymerization reaction was carried out at 85°C for 3 hours in 165.18g of ethanol (Fujifilm Wako Pure Chemical Co., Ltd.). After the polymerization reaction was completed, the mixture was dried at normal pressure at 85°C for 1 hour. Then, the mixture was dried under reduced pressure at 60°C for 1.5 hours to obtain a concentrate. 696.35g of methanol (Fujifilm Wako Pure Chemical Co., Ltd.) was added to the concentrate and stirred for 30 minutes. After stirring, the mixture was left to stand for 1 hour, and the supernatant was removed by decantation. The precipitate was dried at normal pressure at 85° C. for 30 minutes, and then dried under reduced pressure at 40° C. for 1 hour to obtain copolymer 3.
[0064] Comparative Example 2 94.27g of methoxytriethylene glycol acrylate (MTEGA) (Shin-Nakamura Chemical Co., Ltd.), 15.60g of silicone methacrylate (PDMSMA) (Gelest, product name: MCR-M11) and 138.66g of 2-ethylhexyl acrylate (EHA) (Toa Gosei Co., Ltd.) were added with 0.2465g of azobisisobutyronitrile (AIBN) (Fujifilm Wako Pure Chemical Co., Ltd.), and polymerization reaction was carried out at 85°C and 3 hours in 580.03g of ethanol (Kishida Chemical Co., Ltd.). After the polymerization reaction was completed, the mixture was dried at normal pressure at 85°C for 1 hour. Then, the mixture was dried under reduced pressure at 60°C for 1.5 hours to obtain a concentrate. The concentrate was divided into two equal parts, concentrate A and concentrate B. Next, 632.00g of methanol (Kishida Chemical Co., Ltd.) was added to 122.53g of concentrate A, and the mixture was stirred at room temperature for 30 minutes. After the stirring, the mixture was left to stand for 1.5 hours, and the supernatant was removed by decantation. Methanol was added to the precipitate, and the mixture was stirred at room temperature for 30 minutes. After leaving the mixture to stand for 1.5 hours, the supernatant was removed by decantation. This process was repeated three times to obtain precipitate A. The amounts of methanol used were 632.09g, 632.09g, and 632.32g, respectively. The obtained precipitate A was dried at normal pressure at 85°C for 30 minutes, and then dried under reduced pressure at 40°C for 1 hour to obtain copolymer 4.
[0065] As shown in Tables 1 and 2, when an evaluation sheet was prepared using the copolymer of the embodiment having a high reduced viscosity and weight average molecular weight, good results were obtained in the blood coagulation test after alcohol immersion treatment. It is presumed that the copolymer of the embodiment has a higher reduced viscosity than the conventional (meth)acrylate copolymer, and therefore the coating thickness becomes more uniform. The mechanism is shown in Table 3.
[0066] That is, when the copolymer of the embodiment is coated, the water in the air that adheres to the upper surface of the coating is delocalized when the ethanol is removed, so the coating thickness becomes uniform. It is presumed that the subsequent alcohol immersion treatment suppresses the occurrence of uncoated surfaces (defects such as coating spots). It was also found that the copolymer of the embodiment has sufficient durability against dissolution in blood.
[0067] [Table 1]
[0068] [Table 2]
[0069] [Table 3]
[0070] It was found that the material of the present invention maintained good blood compatibility even after immersion in alcohol for 16 hours at room temperature, demonstrating that the material can maintain blood compatibility for a longer period of time compared to conventional antithrombotic materials. [Industrial Applicability]
[0071] The copolymer of the present invention can be used as a material having excellent blood compatibility and high hydrophilicity. In addition, since the physical properties of the material are a water-insoluble viscous substance, it can provide a material that can be used to coat the entire blood circuit without impairing the physical properties of medical equipment. Therefore, it will greatly contribute to the development of the industry.
Claims
1. A (meth)acrylate copolymer having a weight average molecular weight of 60,000 or more and 500,000 or less, which is obtained by copolymerizing alkyl (meth)acrylate units represented by the following general formula 1, silicone (meth)acrylate units represented by the following general formula 2, and methoxypolyethylene glycol (meth)acrylate units represented by the following general formula 3 in a molar ratio of 80 to 20 / 10 to 0.01 / 10 to 79.99, and which is water-insoluble (here, water-insoluble means that the (meth)acrylate an antithrombotic material comprising a (meth)acrylate copolymer which is in a viscous liquid state at room temperature, soluble in any one of alcohols having 1 to 6 carbon atoms, has a residual monomer amount of 4,000 ppm or less, and has a reduced viscosity (ηsp / c) of 0.18 dl / g or more and 0.50 dl / g or less (meaning that when 1 mass % of the copolymer is allowed to stand in 99 mass % physiological saline at 37°C for 30 days, the mass loss rate of the copolymer is 1 mass % or less); 【Chemistry 1】 (In the formula, R 1 is an alkyl group having 8 to 12 carbon atoms; R 2 represents a hydrogen atom or a methyl group) 【Chemistry 2】 (In the formula, R 3 is a hydrogen atom or a methyl group, R 4 is an alkylene group having 1 to 6 carbon atoms, R 5 represents an alkyl group having 1 to 6 carbon atoms, and n represents an integer of 1 to 30. 【Chemistry 3】 (In the formula, R 6 represents a hydrogen atom or a methyl group, and n represents an integer of 2 to 4.
2. A medical device comprising the antithrombotic material according to claim 1.
Citation Information
Patent Citations
Phosphorylcholine analog containing polymer and application
JP2002356519A
Antithrombotic antibacterial composition and medical tool
JP2008266225A
Antithrombogenic material
JP2008289864A
Catheter
JP2009261437A
Antithrombotic materials
JP4793700B2